Girls' Schooling Choices and Home Production: Evidence from Pakistan - Hugo Reis (Institute for the Study of Labor (IZA), 2015)
The paper develops and estimates a dynamic structural model that allows for the interrelations between girls' schooling and mothers' labor market participation decision, in a rural area of Pakistan where drop-out rates are considerably high. The model incorporates home production, which is critical for understanding the behavior of mothers when deciding girls' schooling. Results suggest that monetary incentives are a good mechanism to increase girls' school enrollment, but not the most cost effective. The impact of the conditional cash transfer program on secondary school enrollment rate was only one third of the impact of the school building program. Regarding welfare, the difference between schemes is smaller. Results also highlight the effectiveness of the role of conditionality.
Keywords: I25; I28; 330; girls' schooling; home production; development economics; structural model; discrete choice dynamic programming models